Online Customer Experience and Its Relationship to Repurchase Intention: An Empirical Case of Online Travel Agencies in China. Issue 10 (2nd October 2016) - Liu, Yan; Pu, Bo; Guan, Zhenzhong; Yang, Qizhi
ABSTRACT: The study reported here examines the relationship between flow experience and repurchase intention by focusing on the joint mediating effects of loyalty. Data were taken from a survey of shopping experiences, at online travel websites, of 325 customers in China. The results show that flow experience has a significant effect on repurchase attention. Moreover, interactive speed, skill, challenge, perceived control, telepresence, perceived usefulness, and perceived ease of use are positively related to flow experience. Lastly, the findings show that loyalty, to some extent, acts as a mediator between flow experience and repurchase attention.